CHAORDIC ENTREPRISE: SEBUAH PENGANTAR - Fransisca Mulyono (Bina Ekonomi, 2010)
Business environment nowadays, that becoming more and more turbulent and complex, is hard to be predicted by managements since it has the butterfly effect : the effect that brings  the greater effect in other places in this world when there  is a change  in a certain  place. Traditional organization that considering employees as an object with its rigid structure cannot adjust these rapid changes properly.  It needs to be replaced by a new alternative organization: chaordic organization, i.e. an organization that combines chaos and order situation in the same time to bring changes in management as an anticipation to its environment. Chaordic organization  is very important for business  today because of its high appreciation  on human  resources making everybody  in all units of organization have a high degree on autonomy  and  freedom, and as a result be the leading  creative  and  innovative  organization.Key words : turbulensi,  kompleksitas, kreativitas,  inovasi, chaordic.